Nonisocyanate polyurethane/silica hybrid coatings via a sol-gel route - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY-HINDAWI, 2012)
Polyurethane/silica hybrids by a nonisocyanate route were prepared by reacting cyclic carbonate-modified bis(4-glycidyloxy phenyl)phenyl phosphine oxide (BGPPO), and poly(propyleneglycol)diglycidyl ether (PPG-DGE) with hexamethylene diamine. The incorporation of silica was achieved via a solgel method. The effect of silica and phosphine oxide moiety on polyurethane coating properties was studied by physical, mechanical, and thermal tests. Modulus and hardness of the coatings were enhanced by increasing the amount of silica and phosphine oxide based resin. The improvement in flame retardancy and thermal stability of nanocomposites was proved with increased char yield values and decomposition temperatures in thermogravimetric analyses. (C) 2011 Wiley Periodicals, Inc. Adv Polym Techn 31: 390400, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.20262
Keywords: Nonisocyanate route; Organic-inorganic hybrid; Phosphine oxide; Polyurethane; Sol-gel; PHOSPHORUS-CONTAINING EPOXY; FLAME-RETARDANT; PHOSPHINE OXIDE; SILICON; RESINS; NANOCOMPOSITES